Two cases with fulminant type 1 diabetes that developed long after cessation of immune checkpoint inhibitor treatment. Issue 8 (29th April 2022) - Hatayama, Satoko; Kodama, Shinjiro; Kawana, Yohei; Otake, Sonoko; Sato, Daiki; Horiuchi, Takahiro; Takahashi, Kei; Kaneko, Keizo; Imai, Junta; Katagiri, Hideki
ABSTRACT: Various immune‐related adverse events (irAEs), including fulminant type 1 diabetes (FT1D), are known to be associated with immune checkpoint inhibitors (ICIs). We experienced two lung adenocarcinoma cases who developed fulminant type 1 diabetes long after discontinuation of ICI therapies. One, a 74‐year‐old male, received nivolumab and developed fulminant type 1 diabetes 44 days after the last infusion. The other, an 85‐year‐old male, received atezolizumab and developed fulminant type 1 diabetes 171 days after the last infusion. Clinical ICI treatment guidelines recommend laboratory tests during ICI treatments but the necessity of tests in patients whose ICI therapy has been discontinued is not clearly described. These cases indicate that blood glucose monitoring should be continued at least for several months, and that patients should be informed of the possibility of fulminant type 1 diabetes after ICI discontinuation, because fulminant type 1 diabetes progresses rapidly and can be life‐threatening if not promptly recognized.